Divergence between bread wheat and Triticum militinae in the powdery mildew resistance QPm.tut-4A locus and its implications for cloning of the resistance gene - Janáková, Eva; Jakobson, Irena; Peusha, Hilma; Abrouk, Michael; Škopová, Monika; Šimková, Hana; Šafář, Jan; Vrána, Jan; Doležel, Jaroslav; Järve, Kadri; Valárik, Miroslav (Theoretical and Applied Genetics, 2019)
A segment of Triticum militinae chromosome 7G harbors a gene(s) conferring powdery mildew resistance which is effective at both the seedling and the adult plant stages when transferred into bread wheat (T. aestivum). The introgressed segment replaces a piece of wheat chromosome arm 4AL. An analysis of segregating materials generated to positionally clone the gene highlighted that in a plant heterozygous for the introgression segment, only limited recombination occurs between the introgressed region and bread wheat 4A. Nevertheless, 75 genetic markers were successfully placed within the region, thereby confining the gene to a 0.012 cM window along the 4AL arm. In a background lacking the Ph1 locus, the localized rate of recombination was raised 33-fold, enabling the reduction in the length of the region containing the resistance gene to a 480 kbp stretch harboring 12 predicted genes. The substituted segment in the reference sequence of bread wheat cv. Chinese Spring is longer (640 kbp) and harbors 16 genes. A comparison of the segments' sequences revealed a high degree of divergence with respect to both their gene content and nucleotide sequence. Of the 12 T. militinae genes, only four have a homolog in cv. Chinese Spring. Possible candidate genes for the resistance have been identified based on function predicted from their sequence.
Keywords: Genetic Loci; Ascomycota; Triticum; nemoci rostlin; mapování chromozomů; Chromosome Mapping; odolnost vůči nemocem; Disease Resistance; chléb; Chromosomes, Plant; chromozomy rostlin; Genetic Variation; rostlinné geny; Cloning, Molecular; anotace sekvence; Plant Diseases; Molecular Sequence Annotation; klonování DNA; pšenice; genetické lokusy; genetická variace; Genes, Plant; Bread